ANALISIS INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Hasan, Hasan (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2011)
The current development of Islamic banking industry in Indonesia is rapidly growing. This article analyzes the Islamic banking industry in Indonesia using Porter’s five-forces competitive industry approach. Each of the power industry are discussed. The conclusion indentifies Islamic banking industry conditions that need to be considered.